2004
DOI: 10.21236/ada428279
|View full text |Cite
|
Sign up to set email alerts
|

Crime Self-Reporting Study: Phase 1

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to Department of Defense, Washington Headquarters Services, Directorate for I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Miscoded data were cleaned both manually and electronically using Microsoft Visual Basic macros. More detailed descriptions of the method of coding ROIs are provided in Buck (2004) and Buck and Rose (2004). An excerpt from Buck (2004) is provided in Appendix B.…”
Section: Coding Results Of "Any Criminal Offense" Using Rois Of Crimimentioning
confidence: 99%
See 1 more Smart Citation
“…Miscoded data were cleaned both manually and electronically using Microsoft Visual Basic macros. More detailed descriptions of the method of coding ROIs are provided in Buck (2004) and Buck and Rose (2004). An excerpt from Buck (2004) is provided in Appendix B.…”
Section: Coding Results Of "Any Criminal Offense" Using Rois Of Crimimentioning
confidence: 99%
“…Research by PERSEREC has shown that a significant proportion of subjects do not self-disclose offenses as required in their security clearance applications (Buck & Reed, 2003;Buck & Rose, 2004). For these reasons, access to the NDR would, through an efficient means, improve the effectiveness of personnel security clearance investigations by surfacing information that may bear on individuals' suitability and trustworthiness for positions of trust and access to classified information.…”
Section: Introductionmentioning
confidence: 99%